Evaluation of preparation methods for MS‐based analysis of intestinal epithelial cell proteomes. Issue 13 (5th May 2015) - Hesselager, Marianne Overgaard; Codrea, Marius Cosmin; Bendixen, Emøke
<x xml:space="preserve">Abstract</x> The gut epithelium formed between an organism and the environment plays an essential role in host–microbe interactions, yet remains one of the least characterized mammalian tissues. Especially the membrane proteins, which are critical to bacterial adhesion, are understudied, because these proteins are low in abundance, and large amounts of sample is needed for their preparation and for undertaking MS‐based analysis. The aim of this study was to evaluate three different methods for isolation and preparation of pig intestinal epithelial cells for MS‐based analysis of the proteome. Samples were analyzed by LC and electrospray QTOF‐MS. The methods were evaluated according to efficiency, purity, transmembrane protein recovery, as well as for suitability to large‐scale preparations. Our data clearly demonstrate that mucosal shaving is by far the best‐suited method for in‐depth MS analysis in terms of ease and speed of sample preparation, as well as protein recovery. In comparison, more gentle methods where intestinal epithelial cells are harvested by shaking are more time consuming, result in lower protein yield, and are prone to increased technical variation due to multiple steps involved.